Strategic Information Systems Planning (SISP) Practices In Health Care Sectors Of Bangladesh - Hoque, Md. Rakibul; Hossin, Md. Ekram; Khan, Wahiduzzaman (European Scientific Journal, ESJ, 2016)
Strategic Information Systems Planning (SISP) has been a topic of considerable importance and interest to Information Systems (IS) professionals since the 1970's and consistently ranked as a top issue for IS executives in both developed and developing countries. Studies have shown that SISP can assist manager in defining the information systems, develop IS strategy, and allocate resources for IS strategy. However, the use of SISP in healthcare sectors in developing countries like Bangladesh is underdeveloped and under-researched. This study examined the benefits of SISP in healthcare organization in developing countries in general and Bangladesh in particular. This study also focused on the current practice and key implementation challenges of Strategic Information Systems Planning (SISP) in healthcare sectors in developing and transitional economies. Finally, some recommendations are proposed to overcome the challenges using a ‘hybrid’ approach.